Mechanical and tribological properties of plasma sprayed graphene nanosheets/Al2O3+13 wt%TiO2 composite coating. (June 2020) - Feng, Yanhan; Fang, Jianhua; Wu, Jiang; Gu, Kecheng; Liu, Ping
Abstract: Graphene nanosheets/Al2 O3 +13 wt%TiO2 (GNs/AT-13) composite coatings were prepared by plasma spraying. The tribological test was applied on a ball-on-disc tribometer under dry sliding condition, and the friction coefficient and wear rate of the GNs/AT-13 coating decreased by ~13% and ~19%, respectively. A graphene-containing transfer layer was confirmed to exist on the wear scar surface, using energy dispersive spectrometer (EDS) and Raman spectroscopy, which might act as the protective and lubricating layer at the friction interface. Considerable improvements have been observed in the mechanical properties of the GNs/AT-13 coating using Rockwell and Vickers indentors Besides, a denser microstructure was observed in the GNs/AT-13 coating. These indicate that GNs is a promising nanofiller for ceramic coating. Highlights: Graphene nanosheets/Al2 O3 +13%TiO2 (GNs/AT-13) coating is prepared by plasma spray. Graphene nanosheets (GNs) can be well preserved after ultra-high temperature spray. Tribological and mechanical properties of GNs/AT-13 coating significantly improved. A graphene-contained transfer film with anti-friction and anti-wear effect appeared.